Critical factors in the information management process: the analysis of hospital-based patient safety incident reports - Jylhä, Virpi; Bates, David W.; Saranto, Kaija (Finnish Journal of eHealth and eWelfare, 2016)
The purpose of this study is to describe the nature of patient safety incidents relating to information management and to identify critical factors for a safe information management process in a university hospital. A total of 813 information management incidents in hospital-based adverse event reports were analyzed using directed content analysis. Descriptive statistics and cross tabulations were used to quantify the results. The results of this study showed that the majority of incidents occurred during the information distribution phase. The most frequent incidents fell into the category of written information transfer and communication; furthermore, many of these incidents concerned medication data. There was a high amount of inaccurate data and omissions in the different phases of the information management process. Information organization and storage, information distribution, and information use phases are critical in terms of patient safety, and a high proportion of the problems in this area are potentially preventable. It is thus essential to develop more effective strategies to ensure safe information management. The data from this study also suggest that while incident reports can help to identify breakdowns in the information management process, the quality of reporting needs to be improved.